Comparison between Immunocytochemical and Immunofluorescence techniques for Cytomegalovirus Antigenemia Detection in Transplant Recipients - Schroeder, Regina Barbosa (2009)
Introduction: Cytomegalovirus (CMV) infection is a major cause for morbidity among immunossupressed patients in transplant recipients. CMV antigen detection in blood cells by antigenemia test is a good marker for viral reactivation, showing a high clinical correlation. Some improvements has occurred in the last years changing it from an in-house technique to a more practical and standardized test, by the use of commercial kits. Purpose: To make a comparison between immunocytochemical and immunofluorescence techniques to the CMV antigenemia detection in transplant recipients. Methods: It was studied 132 random blood samples from transplant patients, being routinely analyzed for CMV infection. They were simultaneously tested by two different commercial kits for pp65 antigenemia: Immunocytochemical (IHC), based on the antigen detection by an anti-alcaline-phosphatase reaction [APAAP-BIOTEST-Germany], and immunofluorescence (IF), detecting fluorescein positive reaction [BRITE TURBO-IQP-Netherland]. IHC was performed in previously isolated granulocytes by dextran gradient in a 6-hour turn, and IF was performed in total leukocytes spending about 2 hours. Results: Patients had 1±20.1 yeas old, and they were recipients of the following transplants: kidney (n=73; 55.3%), lung (n=34; 25.8%), liver (n=11; 8.3%), hematopoietic stem cell (n=7; 5.3%), kidney-pancreas (n=3; 2.3%) or heart (n=4; 3.0%). The median post-transplant follow-up at the time of the sample collection was 91 days (5 to 2,103 days). IHC technique showed 35.6% (n=47) of positive samples for CMV antigenemia. This rate was 38.6% (n=51) using IF. The median positive-cells was 4.0/100000 granulocytes by IHC (highest: 515 positive-granulocytes), and 5.0/200000 leukocytes by IF (highest: 682 positive-leukocytes). Disagreement occurred in 6 samples (4.5%): 5 IQ false-negative were positive by IF (median=1+cell/ 200000 leukocytes); and 1 false-negative case by IF with positive result when analyzed by IHC (1+cell/100000 granulocytes). The correlation was highly significant (P=0.000) between both techniques, whether among the positive tests (R=0.974) or in the general analysis (R=0.996). Conclusion: Immunocytochemical or immunofluoresce antigenemia is suitable to the pp65 CMV antigen detection in transplant recipients. Regarding the high correlation between them, IF has the advantage to be easier and faster.